Reading Intervention Programmes Employed in EFL Reading Contexts: A Review Article (International Journal of Language, Literacy and Translation, 2025)
Among the four major language skills, reading serves as an important tool for successful academic achievement. Various studies in EFL contexts have focused on the effect of some types of instruction on EFL students’ reading comprehension. The purpose of this paper is to review these studies which have examined the effect of some instructional inputs on the development of reading comprehension among EFL students at both school and tertiary levels. This study is valuable as it sheds lights on intervention programmes that have been employed for the sake of improving reading comprehension in EFL contexts. It further provides some insights that can be useful for future researchers who intend to use reading intervention programmes. This review article has revealed that most of these studies have focused on EFL students in schools. Additionally, this review has shown that most of these studies have not employed full intervention programmes that pay attention to the improvement of students’ reading skills. Rather, each of these studies has just focused on one aspect and examined its effect on students’ reading comprehension. For example, while some studies examined the effect of extensive reading, others have focused on the effect of a selection of cognitive strategies on EFL students’ reading comprehension. This study highlights the need for more studies that should consider the effect of instructional packages such as Cognitive Academic Language Learning Approach (CALLA), task-based instruction, Concept-Oriented Reading Instruction (CORI), extensive reading, and cooperative learning on the development of EFL students’ reading comprehension.